EFFECTIVENESS OF APPLYING GROWTH REGULATORS AT SUGAR BEET CULTIVATION IN THE CENTRAL UKRAINE - Kulyk H. А.; Reznichenko, V. P.; Trykina, N. M.; Malakhovska V. О. (Scientific Progress & Innovations, 2020)
The effectiveness of applying plant growth regulators at sugar beet cultivation has been considered in the article. In modern agricultural production, growth regulators are an integral part of sugar beet growing technologies. The creation of modern growth regulators and results of scientific research give grounds for changing the viewpoints on application of such preparations in agricultural production. There are technolo-gies of applying these preparations both for pre-sowing seed treatment and for spraying growing plants in different phases of vegetation. Growth regulating substances activate physiological processes of sugar beet development, ensure realization of the crop genetic potential, and contribute to reducing the dependence of vegetative process on abiotic factors of the natural environment. As a result, there is an increase in yield and sugar content in the process of optimizing cultivation conditions. In the process of research, growth regula-tors for pre-sowing seed treatment as well as and in combination with the treatment of vegetative plants were applied. During sugar beet seed treatment it was found that growth regulators contributed to the increase of field germination and more intensive plant weight increase during the initial stages of crop growth and de-velopment. According to the indices of sugar beet root weight growth dynamics during vegetation, it was registered that applying plant growth regulators stimulated the increase of this indicator. However, the highest indicator was observed while applying Stimpo and Regoplant growth regulators both for seed treat-ment and for spraying vegetative plants of sugar beet. The productivity of sugar beet depends on many fac-tors, including the application of plant growth regulators. The results of the studies indicate that using growth regulators while cultivating sugar beet is one of the most effective agro-measures to improve crop productivity. We found that with complex application of Stimpo and Regoplant growth regulators, signifi-cantly higher yield, sugar content of roots and sugar amount per area unit were obtained.